Combating Unregulated Fishing through Unilateral Trade Measures: A Time for Change in International Fisheries Law? - Urrutia, Osvaldo (Victoria University of Wellington Law Review, 2018)
Unregulated fishing on the high seas – understood as fishing activities by vessels flagged to a non-member state in an area regulated by a regional fisheries management organisation – are a significant threat to the sustainability of high seas fishery resources. The European Union (EU) and the United States – two major market destinations for fishery products – have shown a strong determination to treat unregulated fishing as illegal fishing. They have applied or threatened to apply trade restrictions to states that have no treaty obligations to refrain from fishing on the high seas. These actions are conspicuous because the practical effect of these unilateral measures entails a challenge to the fundamental pacta tertiis rule. This article suggests that the application of unilateral trade-related measures by the EU and the United States against non-member states represents relevant state practice for the formation of a prohibition against unregulated fishing in customary international law.